2012
DOI: 10.1155/2012/567207
|View full text |Cite
|
Sign up to set email alerts
|

Spectrofluorometric Analysis of New-Generation Antidepressant Drugs in Pharmaceutical Formulations, Human Urine, and Plasma Samples

Abstract: Spectrofluorometric analysis for the quantification of new-generation antidepressant drugs belong to the class of selective serotonin reuptake inhibitors and selective norepinephrine reuptake inhibitors is described. Five different drugs, sertraline, paroxetine, citalopram, venlafaxine, and fluoxetine, were analysed for spectrofluorometric detection in pharmaceutical formulations and urine and plasma samples. The calibration curves were found linear between fluorescence intensity and drugs concentration in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The results of this study showed wider linear range, 0.004-10.00 µmol L -1 , and lower LOD, 1.23 µmol L -1 , than methods [4][5][6]. It is less expensive than methods [2,3].…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The results of this study showed wider linear range, 0.004-10.00 µmol L -1 , and lower LOD, 1.23 µmol L -1 , than methods [4][5][6]. It is less expensive than methods [2,3].…”
Section: Resultsmentioning
confidence: 69%
“…Potentiometric chemo sensors for selective determination of sertraline based on the molecular imprinting technique and electrometric methods using voltammetric technique were developed [1][2][3]. Several spectroscopic methods have been reported for the determination of Ser + and their metabolites in pharmaceutical formulation [4][5][6]. Different HPLC methods were reported for the drug.…”
Section: Introductionmentioning
confidence: 99%
“…Urine tests of tricyclic antidepressants are often used in emergency departments in cases of suspected overdose, and in the pain literature for pain management compliance testing 136139. Qualitative urine tests of SSRIs, SNRIs, and bupropion exist, and a number of different methods of detection have been proposed and studied, but to date these tests are not used clinically, and the commercial availability of such tests appears limited 140145…”
Section: Management Of Depression In Patients Misusing Antidepressantsmentioning
confidence: 99%
“…Potentiometric chemo sensor for the selective determination of sertraline based on the molecular imprinting technique and electrometric methods using voltammetric technique were developed [2–4] . Several spectroscopic methods have been reported for the determination of Ser + and their metabolites in its pharmaceutical formulations [5–7] .…”
Section: Introductionmentioning
confidence: 99%